Values of young employees: Z-Generation perception - Jelena Titko; Anna Svirina; Viktorija Skvarciany; Inga Shina (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The current paper aims to analyse the importance of values of young employees now and in five years period. In order to achieve the aim, the questionnaire consisting of fifty statements was developed and disseminated between the Latvian students. The sample size was 392, which shows that the results represent the whole populations. For data processing, factor analysis was chosen as a tool. The data factorability was assessed via Bartlett's Test of Sphericity, Kaiser-Myer- Olkin (KMO) statistic, initial estimates of communality and the anti-image correlation matrix. The factors were extracted via principal axis factoring (PAF). The number of factors was determined by the scree plot/Kaiser's rule and was equal to five in both cases. The results showed the for the young employees the essential values today are those connected to the personality trait. However, in five years, the essential values would be those that are linked to professional development.
Keywords: E24; M51; J13; A13; 650; Z-Generation; values; factor analysis; professional development; employment